Risk analysis of construction planning that affecting quality and time control in the apartment development performance using PLS - SEM method (case study in apartments in Tangerang) - Sumantri, Angga; ., Nunungwidyaningsih; P. K. Bintoro, Bambang (International Journal of Engineering and Technology, 2020)
Large-scale projects, especially construction projects, have a large degree of difficulty in planning and controlling. For the project to work, a rigorous project planning and control analysis is required. This study aims to identifythe relationship between construction planning risk, quality control, time control, and management performance. Three apartment development projects in the Tangerang area were researched and 58 respondents were selected as the research sample. Based on the results of PLS SEM analysis, it was found that the risk of construction planning has a positive and significant effect on quality control and also on time control. Project control in terms of quality and time has a positive influence on management performance in apartment construction. If the company can carry out quality control and time correctly, then management performance will increase, but the performance improvement is not significant.Â Â